2005
DOI: 10.1016/j.msea.2005.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Discrete dislocation modelling of submicron indentation

Abstract: Indentation of a planar single crystal by a circular rigid indenter is analyzed using discrete dislocation plasticity. The crystal has three slip systems and is initially dislocation-free, but edge dislocations can nucleate from point sources inside the crystal. The lattice resistance to dislocation motion, the interaction with point obstacles and dislocation annihilation are incorporated through a set of constitutive rules. Indentation is displacement driven and at each stage of the loading history, a boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 9 publications
1
41
0
Order By: Relevance
“…However, it should be noted that our results mostly deal with the very first stages of plasticity, where interactions among dislocations are not as relevant. Nevertheless, most of these limitations can also be applied to 2D DD, which has been a very useful tool to study size effects in plasticity [34][35][36][37][38][39], Bearing in mind these limitations for 2D, simulations were carried out to understand the effect of temperature and multiaxiality on the yield stress defined as stress necessary to nucleate stable dislocations from the void surface and on the kinetics of void growth. They were compared with previous results of 3D MD and 2D DD simulations to establish a map of mechanisms and size effects for void growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that our results mostly deal with the very first stages of plasticity, where interactions among dislocations are not as relevant. Nevertheless, most of these limitations can also be applied to 2D DD, which has been a very useful tool to study size effects in plasticity [34][35][36][37][38][39], Bearing in mind these limitations for 2D, simulations were carried out to understand the effect of temperature and multiaxiality on the yield stress defined as stress necessary to nucleate stable dislocations from the void surface and on the kinetics of void growth. They were compared with previous results of 3D MD and 2D DD simulations to establish a map of mechanisms and size effects for void growth.…”
Section: Introductionmentioning
confidence: 99%
“…In these simulations, ''low source density'' materials were considered with the plasticity size effect mainly resulting from sourcelimited plasticity. Widjaja et al (2005Widjaja et al ( , 2006 reported on two-dimensional simulations for the cylindrical indentation of materials with a wide range of source densities. Over the range of indentation depths considered in these studies, the increasing hardness with increasing indentation depth associated with sharp indenters was not obtained and the cylinder radius played a dominant role.…”
Section: Introductionmentioning
confidence: 99%
“…This condition is not required in the crystal plasticity calculations because they maintain symmetry about x 1 = 0. The connection between the stress state in the body and the evolution of the dislocation structure is given through a set of constitutive equations, similar to the ones proposed in [26] and used previously in [13] as well as in related investigations, [3,4,27]. These rules control the nucleation, glide, annihilation of dislocations as well as their pinning at obstacles.…”
Section: Discrete Dislocation Plasticitymentioning
confidence: 99%
“…This is precisely the range in which plastic deformation of crystalline solids is known to be size dependent and thus not adequately described by conventional continuum plasticity theory. Discrete dislocation plasticity simulations have proven to be capable of capturing size-dependent plasticity in various situations, including (sub)micron-indentation with single indenters [1][2][3][4]. Recent models of contact between elastic-plastic rough surfaces have shown that interactions between neighboring asperity contacts play a critical role in determining the true area of contact between the surfaces [5][6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation